PERLINDUNGAN HUKUM BAGI PEKERJA PERJANJIAN KERJA WAKTU TERTENTU (PKWT) PERSPEKTIF HAM DALAM ISLAM ABDULLAHI AHMED AN-NA’IM - Muhammad Makhmuri; Mahbub Ainur Rofiq (Muslim Heritage, 2022)
AbstractThe legal protection for PKWT workers is apprehensive, even to the point where a new policy was issued through Law Number 11 of 2020 on Job Creation and its implementing regulations. Legal protection of basic human rights is crucial as is the case in the thought of human rights in Islam Abdullahi Ahmed an-Na'im. The purpose of this study is to find out in-depth how the legal protection for PKWT workers is in the Job Creation Act and the implementing rules from the perspective of human rights fiqh according to Abdullahi Ahmed an-Na'im. This research is normative legal research with a statute approach and conceptual approach. The data in this study are secondary in the form of primary, secondary, and tertiary legal materials. The results of this study indicate that the Job Creation Act and its implementing regulations have not fully provided legal protection for PKWT workers, especially in terms of PKWT based on the completion of a certain job and the elimination of legal consequences if the PKWT is made unwritten. The provisions in Abdullahi Ahmad an-Na'im's human rights in Islam concept do not reflect the spirit of reciprocity and do not fulfill the right to life and freedom, so the values of sharia humanism as when they were revealed in Mecca have not been embodied in the policy of PKWT workers in the new regulation. AbstrakPerlindungan hukum bagi pekerja PKWT terbilang memprihatinkan, bahkan sampai pada lahirnya kebijakan baru melalui Undang-Undang Nomor 11 tahun 2020 tentang Cipta Kerja dan aturan pelaksananya. Perlindungan hukum terhadap hak-hak dasar manusia adalah hal yang krusial seperti halnya dalam pemikiran HAM dalam Islam Abdullahi Ahmed an-Na’im. Tujuan penelitian ini untuk mengetahui secara mendalam bagaimana perlindungan hukum terhadap pekerja PKWT dalam Undang-Undang Cipta Kerja dan aturan pelaksananya perspektif HAM dalam Islam menurut Abdullahi Ahmed an-Na’im. Penelitian ini adalah penelitian hukum normatif dengan pendekatan perundang-undangan dan konseptual. Data dalam penelitian ini berasal dari data sekunder yaitu bahan hukum primer, sekunder, dan tertier. Hasil penelitian ini menujukan bahwa Undang-Undang Cipta Kerja dan aturan pelaksananya belum sepenuhnya memberikan perlindungan hukum terhadap pekerja PKWT terutama dalam ketentuan PKWT berdasarkan selesainya suatu pekerjaan tertentu dan penghapusan konsekuensi hukum apabila PKWT dibuat secara tidak tertulis. Ketentuan tersebut dalam konsep HAM dalam Islam Abdullahi Ahmed an-Na’im justru belum mencerminkan spirit resiprositas dan tidak memenuhi hak untuk hidup dan bebas, sehingga nilai-nilai humanisme syariah seperti saat diturunkan di Makkah belum terjewantahkan dalam kebijakan pekerja PKWT pada regulasi baru tersebut.